Educación y nuevas tecnologías en la práctica docente. - Barahona Hidalgo, Diana Paulina (2016)
This article aims to highlight the shortcomings in education using the ICT inside teaching practicing and likewise propose communication strategies that allow the inclusion of new technologies in education. Our case study framed in media education and new technologies in teaching is limited to an analysis using experience as a virtual tutor training processes for teachers in the ICT 1 issued by the Agencia Universitaria para la Gestión Del Conocimiento (AUGE), it proposes changes in the paradigm of learning and creates innovative processes in teaching practice. It is proposed to use a qualitative methodology that focuses on an interpretative and subjective process using tools applied in teaching practices. Teaching practices must be innovative and substantial around learning, therefore educators must interpret all languages and content they require to be understood when used as tools within or outside the classroom. The proposal is then encourage the exchange of educational development from communication, it using ICT in a playful and specifically way, about learning that education requires current models around the student and teacher; students generate discerning, thoughtful and know classified information. The best way that ICTs can be used in teaching is understanding them since birth as a tool that goes far beyond the use of the computer.